2002
DOI: 10.1080/08827510212341
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency Noise of Tantalum Capacitors

Abstract: A low frequency noise and charge carriers transport mechanism analysis was performed on tantalum capacitors in order to characterise their quality and reliability. The model ofTa−Ta2O5−MnO2MIS structure was used to give physical interpretation of VA characteristic both in normal and reverse modes. The self-healing process based on the high temperatureMnO2−Mn2O3transformation was studied and its kinetic determined on the basis of noise spectral density changes. The correlation between leakage current and noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The PF effect has also been observed in Ta capacitors at normal bias with either in-situ PEDOT or MnO 2 cathodes, in which the leakage is significant. 7,16,29 However, for Ta capacitors under normal bias with pre-polymerized PEDOT cathodes, we have shown in Fig. 3 that the leakage current is very low and has a weak voltage dependence over a large range of applied voltage.…”
Section: Resultsmentioning
confidence: 79%
“…The PF effect has also been observed in Ta capacitors at normal bias with either in-situ PEDOT or MnO 2 cathodes, in which the leakage is significant. 7,16,29 However, for Ta capacitors under normal bias with pre-polymerized PEDOT cathodes, we have shown in Fig. 3 that the leakage current is very low and has a weak voltage dependence over a large range of applied voltage.…”
Section: Resultsmentioning
confidence: 79%
“…In terms of thermionic emission, the presence of these traps causes a strong band bending to occur to a degree far greater than that occurring in a non-ideal diode. In the work of Sikula et al [39,64] the activation energy of niobium oxide thin films for the impurity band has been reported as ∼0.9 eV and Hutchins et al [79] have reported an activation energy value of ∼0.62 eV for WO 3 based thin films. Thus, we can observe a consistent correlation between the energy of these traps in this work and those in the literature, verifying our proposed theory.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…Assuming that the TE mechanism is valid across the selected temperature range shown in figure 7, by using equation ( 1), a linear extrapolation of the semi-log I-V data results in a calculated value of 36.64 for η at 25 • C. This value could indicate that the presence of a high defect density at the interface significantly above that which is achieved from flat Nb 2 O 5 thin films [39,64], as η is regarded as an approximation of the defect density. With increasing temperature, the ideality factor decreases, which can be explained by the effective passivation of traps through recombination with thermal carriers.…”
Section: Electrical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation